Benzophenone derivatives from Garcinia livingstonei and their antioxidant activities. (December 2016) - Muriithi, Eva; Bojase-Moleta, Gomotsang; Majinda, Runner R.T.
Graphical abstract: Highlights: Fourteen compounds were isolated. Two new benzophenone derivatives were isolated. The benzophenone derivative1 exhibited better antioxidant activity than vitamin C. Abstract: Two new benzophenone derivatives 4, 3′, 4′-trihydroxy-2, 6-dimethoxybenzophenone1 and its glycoside 3′-β-d -glucosyloxy-4, 4′-dihydroxy-2, 6-dimethoxy-benzophenone2 were isolated from the twigs and stem wood of Garcinia livingstonei together with twelve known compounds. The antioxidant activity of the isolates and extracts was evaluated.